Overview of Dry Eye Disease for Primary Care Physicians - Jeonghyun Kwon; Amirhossein Moghtader; Christie Kang; Zahra Bibak Bejandi; Sumaiya Shahjahan; Ahmad Alzein; Ali R. Djalilian (Medicina)
Dry eye disease (DED), also known as keratoconjunctivitis sicca, is a multifactorial ocular disease characterized by tear film insufficiency due to diverse etiologies including aging, incomplete and infrequent blinking, hormonal changes, medications, and systemic diseases. Classified into aqueous-deficient dry eye (ADDE), evaporative dry eye (EDE), and mixed subtypes, DED presents with symptoms such as irritation, stinging, redness, foreign body sensation, sensitivity to light, and blurred or fluctuating vision. While rare, severe cases may lead to vision loss. With its rising global prevalence across age groups, DED poses a significant public health challenge. Primary care physicians (PCPs), often the first point of contact for DED patients, require timely screening and management strategies. This review explores the epidemiology, pathophysiology, clinical manifestations, diagnosis, and management of DED, emphasizing practical approaches for PCPs. This narrative review was conducted by searching MEDLINE, PubMed, and Google Scholar databases for relevant articles. Diagnostic approaches, including detailed history taking, patient-reported questionnaires, differential diagnosis, and assessments are discussed alongside management strategies, including symptomatic ophthalmic treatment, risk factor mitigation (e.g., reduced digital device screen time), prevention, and nutrition. By providing a synopsis of early symptoms that PCPs are often the first to encounter, practical approaches to screening and managing DED in the primary care setting, and guidelines on when to refer to specialty care, this comprehensive review aims to equip PCPs with the knowledge to improve DED screening and optimize patient outcomes.